POPULASI HAMA WERENG HIJAU (Nephotettix spp.) DAN WERENG PUNGGUNG PUTIH (Sogatella furcifera Horv.) PADA TANAMAN PADI SAWAH DI KECAMATAN SONDER KABUPATEN MINAHASA - Magdalena M. Kesek; Jantje Pelealu; Noni N. Wanta; Juliet M.E. Mamahit (COCOS, 2016)
ABSTRACT  The study aims to determine the abundance of green leafhopper (Nephotettix spp.) pest populations and white back planthopper (Sogatella furcifera Horv.) in rice in the District Sonder.  This research was conducted in two villages of Tincep and Kauneran during the six months from November 2014 through April 2015.  This  study used a survey method in rice crops in two villages. Every village observations determined three plots were divided into five subplots of observations for sampling. Research shows that green leafhopper populations in rice cultivation is  highest in the third observation, in the tincep village is 10,40 tail and village kauneran 9,33 tail. Lowest population occurred when the first observation in the Tincep village 5,06 tail and Kauneran 4,13 tail. Whereas the population of white back planthopper in rice crops in highest in the first observation that, in the village of kauneran 6,26 tail and in village Tincep 6,20 tail. Lowest population occurs on the last observation is at kauneran villages 2,20 tail and Tincep village 1,80 tail. Basides  green leafhopper and white back planthopper found also other insects both as pests and natural enemies.